Associations of diabetes-related distress, depression, medication adherence and health-related quality of life with HbA1c, blood pressure and lipids in adult patients with type 2 diabetes: a cross-sectional study - Chew, Boon How; Mohd Sidik, Sherina; Hassan, Noor Hasliza (Dove Medical Press, 2015)
This study examined the associations of diabetes-related distress (DRD), depressive symptoms, health-related quality of life (HRQoL), and medication adherence with glycemia, blood pressure (BP), and lipid biomarkers in adults with type 2 diabetes mellitus (T2D). This cross-sectional study was conducted in three Malaysian public health clinics in 2012–2013, recruited adult patients (aged ≥30 years) with T2D who had been diagnosed for more than one year, were on active follow-up, and had recent blood test results. Univariable and multivariable analyses were performed to identify significant associated factors for glycated hemoglobin (HbA1c) BP, and lipids. The response rate was 93.1% (700/752). The majority were females (52.8%), Malay (52.4%), and married (78.7%). DRD correlated with systolic BP (r= -0.16); depressive symptoms correlated with low-density lipoprotein cholesterol (r=0.12) and total cholesterol (r=0.13); medication adherence correlated with HbA1c (r= -0.14) and low-density lipoprotein cholesterol (r= -0.11); and HRQoL correlated with casual blood glucose (r= -0.11), high-density lipoprotein cholesterol (r= -0.13), and total cholesterol (r= -0.08). Multivariable analyses showed that HRQoL was significantly associated with casual blood glucose (adjusted B= -0.06, P=0.024); DRD was associated with systolic BP (adjusted B= -0.08, P=0.066); depressive symptoms were associated with low-density lipoprotein cholesterol (adjusted B=0.02, P=0.061), and medication adherence was associated with HbA1c (adjusted B= -0.11, P=0.082) and total cholesterol (adjusted B= -0.06, P=0.086). There were significant and distinctive associations of DRD, depressive symptoms, HRQoL, and medication adherence with glycemia, BP, and lipid biomarkers. Unexpected beneficial therapeutic effects of DRD on BP require further study. A multidisciplinary approach may be needed for risk management in adults with T2D at the primary care level.